2015
DOI: 10.1038/jcbfm.2015.21
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced Neuroinflammatory White-Matter Injury Reduced by Minocycline in SHR/SP

Abstract: Hypertensive small vessel disease is a major cause of vascular cognitive impairment (VCI). Spontaneously hypertensive/stroke prone rats (SHR/SP) with unilateral carotid artery occlusion (UCAO) and a Japanese permissive diet (JPD) have white-matter (WM) damage similar to that seen in VCI. We hypothesized that WM injury was due to hypoxia-mediated, blood-brain barrier (BBB) disruption. Twelve-week-old SHR/SP had UCAO/JPD and were studied with immunohistochemistry, biochemistry, multimodal magnetic resonance imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(125 citation statements)
references
References 39 publications
8
114
0
3
Order By: Relevance
“…112 Recently our group has found that elevation of hypoxia-inducible factor-1 precedes white matter injury and neuroinflammation, leading to edema and BBB disruption in an animal model of VCI. 113 Consistently, reports of hemoglobin (Hgb), a major component of red blood cells known to increase blood O 2 carrying capacity by 70%, 114 was significantly decreased in the red blood cells of AD patients as compared with non-AD controls. 115 In the early stages of AD, reduced Hgb reactivity has been found in practically all the neurons containing p-tau, NFTs, and -synuclein, while Hgb expression was preserved in neighboring healthy neurons.…”
Section: Mechanisms Of Hypoperfusion-induced Neuroinflammation Insupporting
confidence: 72%
“…112 Recently our group has found that elevation of hypoxia-inducible factor-1 precedes white matter injury and neuroinflammation, leading to edema and BBB disruption in an animal model of VCI. 113 Consistently, reports of hemoglobin (Hgb), a major component of red blood cells known to increase blood O 2 carrying capacity by 70%, 114 was significantly decreased in the red blood cells of AD patients as compared with non-AD controls. 115 In the early stages of AD, reduced Hgb reactivity has been found in practically all the neurons containing p-tau, NFTs, and -synuclein, while Hgb expression was preserved in neighboring healthy neurons.…”
Section: Mechanisms Of Hypoperfusion-induced Neuroinflammation Insupporting
confidence: 72%
“…134 In the SHR/SP with the Japanese permissive diet and unilateral carotid artery occlusion, treatment with minocycline blocked the full development of white-matter injuries seen on MRI and improved behavior in the Morris water maze. 135 Based on mouse models of CADASIL, targeting the synthesis of NOTCH3 or the clearance of NOTCH3ECD deposits, might represent a first therapeutic option. 136 Upregulation of Kv1 channels in cerebral arteries has been shown to be the molecular mechanism underlying the diminished myogenic responses in mutant mice.…”
Section: Treatments In Animal Modelsmentioning
confidence: 99%
“…We compared the FA/ADC values of our ARE model with those from a chronic white matter injury model (UCAO-JPD animals) as a representative of irreversible vasogenic edema. 18,26 The UCAO-JPD model has previously been shown to produce irreversible IgG leakage and demyelination in the corpus callosum (CC). 18,26 As expected, we saw a large increase of the ADC in the UCAO-JPD animals, suggesting the presence of vasogenic edema (Figure 2(e)).…”
Section: Brains Of Are Model Showed a Reversible Increase Of Famentioning
confidence: 99%
“…18,26 The UCAO-JPD model has previously been shown to produce irreversible IgG leakage and demyelination in the corpus callosum (CC). 18,26 As expected, we saw a large increase of the ADC in the UCAO-JPD animals, suggesting the presence of vasogenic edema (Figure 2(e)). On the contrary, the FA decreased in UCAO-JPD animals (Figure 2(c)).…”
Section: Brains Of Are Model Showed a Reversible Increase Of Famentioning
confidence: 99%